Mindfulness Correlates with Stress and Coping in University Students - Miller, Carlin J; di Pierdomenico, Emily-Ann; Kadziolka, Marta (Canadian Journal of Higher Education, 2017)
Mindfulness has received significant attention in the empirical literature during the past decade, but few studies have focused on mindfulness in university students and how it may influence problematic behaviours. This study examined the relationships among mindfulness, coping, and physiological reactivity in a sample of university students. Participants completed questionnaires, and skin conductance measurements were collected during an interview where they recalled a personally stressful event. Correlation analyses tested relationships among these variables. There was a negative correlation between substance use and mindfulness. Specifically, those using substances as a coping mechanism were less likely to be mindful and displayed higher physiological reactivity. More mindful individuals were less likely to report misusing substances and were able to calm themselves more quickly than their counterparts following a stressful event. Thus, poor outcomes for distressed students may be reduced with mindfulness-based interventions.